Reading Hebrew Bible narratives - Dearman, John Andrew (Essentials of biblical studies, 2018)
'Reading Hebrew Bible Narratives' introduces readers to narrative traditions of the Old Testament and to methods of interpreting them. Considering literary analysis, words and texts in context, and reception history, this volume gives students an overview of how exegesis illuminates stories in the Bible